Cross-Border Access to Clinical Trials in the EU: Exploratory Study on Needs and Reality - Lalova, Teodora; Padeanu, Cristina; Negrouk, Anastassia; Lacombe, Denis; Geissler, Jan; Klingmann, Ingrid; Huys, Isabelle (Frontiers in Medicine, 2020)
Objectives: To analyze the current situation of cross-border access to clinical trials in the EU with an overview of stakeholders’ real-life experience, and to identify the needs, challenges and potential for facilitation of cross-border access. Methods: We employed a mixed methods design. Semi-structured interviews and an online survey were conducted with a wide range of stakeholders: patient representatives, investigators/physicians, policy and regulatory experts, academic and commercial sponsor representatives, ethics committee members. Interviews underwent a framework analysis. The survey was analyzed descriptively. Results: 396 individuals responded to the survey. The majority were investigators/physicians (46%) and patient representatives (33%). 38 individuals were interviewed. The majority were investigators/physicians (29%) and patient representatives (29%). All European regions were represented in the study. The highest response rate was received from residents of Western European countries (38% of survey respondents, 45% of interviewees), the lowest from Eastern Europe (9% of survey respondents, 5% of interviewees). The study suggested that cross-border participation in clinical trials occurs in practice, however very rarely. 92% of survey respondents and the majority of interviewees perceived as needed the possibility to access clinical trials abroad. However, most interviewees also opined that patients ideally should not have to travel in order to access experimental treatment. The lack of access to treatment in the home country of the patient was described as the main motivation to participate in a clinical trial in another country. The logistical and financial burden for patients was perceived as the biggest challenge. Different stakeholders expressed diverging opinions regarding the allocation of financial and organizational responsibility for enabling cross-border access to clinical trials. Participants provided a number of proposals for improving the current system, which were carefully evaluated by the research team and informed future recommendations. Conclusions: Participation in clinical trials abroad is happening rarely but should be facilitated. There was a consensus on the need for reliable and accessible information regarding practical aspects, as well as multi-stakeholder, multi-national recommendations on existing options and best practice. Broader interdisciplinary research is recommended before discussing options in the EU legislative framework to enable clearly defined conditions for cross-border access to clinical trials.